Spirometric measurement among polyurethane foam mattress-making workers of India - Rajnarayan Ramshankar Tiwari; Sampathraju Raghavan (Wolters Kluwer Medknow Publications, 2021)
Background: The polyurethane foam (PUF) mattress-making workers are exposed to isocyanates which are known respiratory toxicants and cause effect on pulmonary volumes and flows. Thus, the study was with a rationale to measure the changes in pulmonary flow and volumes due to isocyanates among PUF mattress-making workers. Materials and Methods: The study included 183 male workers from seven PUF making units of western and northern India. Using the interview technique as a tool for data collection, demographic and occupational details of the subjects were recorded on the predesigned and pretested pro forma. The mean of spirometric parameters was compared using one-way ANOVA and t-test. The relation between spirometric parameters and anthropometric parameters was analyzed using the correlation coefficient. Results: The spirometry showed that out of 183 participants, 165 (90.2%) subjects had normal spirometry, 13 (7.1%) had restrictive impairment, and 4 (2.2%) had obstructive impairment. All the mean spirometric values showed a declining trend with increasing age, while only forced expiratory volume in first second and forced vital capacity25%-75% showed a declining trend with increasing duration of employment. The spirometric measurements had a negative correlation with age and positive correlation with height. Conclusion: The spirometric values representing the airway flow were affected. The associated factors include age and duration of exposure.